2013
DOI: 10.1080/14685248.2013.864763
|View full text |Cite
|
Sign up to set email alerts
|

A causal continuous-time stochastic model for the turbulent energy cascade in a helium jet flow

Abstract: We discuss continuous cascade models and their potential for modelling the energy dissipation in a turbulent flow. Continuous cascade processes, expressed in terms of stochastic integrals with respect to Lévy bases, are examples of ambit processes. These models are known to reproduce experimentally observed properties of turbulence: The scaling and self-scaling of the correlators of the energy dissipation and of the moments of the coarse-grained energy dissipation. We compare three models: a normal model, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In [31] it has been shown that exponentials of trawl processes are able to reproduce the main stylized features of the (surrogate) energy dissipation observed for a wide range of datasets. Those stylized features include the one-dimensional marginal distributions and the scaling and self-scaling of the correlators.…”
Section: The Energy Dissipationmentioning
confidence: 99%
See 2 more Smart Citations
“…In [31] it has been shown that exponentials of trawl processes are able to reproduce the main stylized features of the (surrogate) energy dissipation observed for a wide range of datasets. Those stylized features include the one-dimensional marginal distributions and the scaling and self-scaling of the correlators.…”
Section: The Energy Dissipationmentioning
confidence: 99%
“…In turbulence it is known (see the reference cited in [31]) that the correlator of the surrogate energy dissipation displays a scaling behaviour for a certain range of lags,…”
Section: The Energy Dissipationmentioning
confidence: 99%
See 1 more Smart Citation
“…[11]. And a recent study [10] of the Helium data discussed in Section 2, based on exponential LSS processes, has revealed a new type of universality for the energy dissipation.…”
Section: Models Of Bss/lss Typementioning
confidence: 99%
“…For instance, Σ could be chosen to be an extIS class of processes σ 2 for which the log σ 2 are trawl process L (A + (t, 0)), as discussed in Section 3 In particular, L may be taken to be an N IG basis, as in [10].…”
Section: Models Of Bss/lss Typementioning
confidence: 99%